Molecular network based on ant colony system via wavelength routers - Taengtang, T.; Praitoonwattanakit, K.; Yupapin, P. P. (My University, 2010)
We propose a new method of molecular transporters generations based on ant colony algorithm for molecular classification and storage applications. The transportation network of molecules via multitweezers inside the close system can be manipulated in the same way of ant colony algorithm relationship. In the proposed method, we assign that each of ants represents an individual tweezer. By using ant colony system, the random codes can be used to communicate between ants inside swarm with pheromone being formed the random network. The quantum state of transporter (individual ant) with different states and wavelengths is represented by the pheromone. In application, this proposal can be an alternative random networking which may be used for communication security, where the fast multiple access may be plausible. © 2010 Wiley Periodicals.
Keywords: Ant colony; Ant network; Dark soliton; Molecular transporter